KERAGAAN PENYULUH PERTANIAN DALAM UPAYA MENDUKUNG PEMBANGUNAN KETAHANAN PANGAN DI KABUPATEN LAMPUNG BARAT - Sri Mustika; Budi Setiawan; Dodik Briawan (Jurnal Gizi dan Pangan, 2008)
The objectives of this research were to know correlation and influence of agricultural extension characteristic to their comprehension about main duty and function and their knowledge about food security. This research was conducted in West Lampung District, using cross sectional design. The method of analysis was descriptive and inferential. There were 58.9% respondents who have a good knowledge of their main duties and about 68.5% respondents who have knowledge about food security. Education and facilities lead to positive correlation with comprehension for knowledge about food security. But in the contrary it was proved that field of expertise and instruction experiences have negative correlation with knowledge for agricultural extension main duties. The other result is that main duties and function of agriculture extension had significant correlation with knowledge of food security, especially for food consumption.